Effect of microbial transglutaminase and setting condition on gel properties of blend fish protein isolate recovered by alkaline solubilisation/isoelectric precipitation. (1st November 2018) - Abdollahi, Mehdi; Rezaei, Masoud; Jafarpour, Ali; Undeland, Ingrid
Summary: The effect of microbial transglutaminase (M‐TGase) (0–0.6 units g −1 sample) and setting condition (25 °C/180 min, 30 °C/120 min, 35 °C/60 min and 40 °C/30 min) on gel properties of blend protein isolate of gutted kilka and silver carp was studied. The protein isolate provided a good substrate for M‐TGase activity so that a low amount of M‐TGase (0.2 unit g −1 sample) substantially improved textural properties and water holding capacity (WHC) of the gels. Breaking force of the gels was positively affected by M‐TGase up to 0.6 unit g −1 sample, but it negatively affected their WHC. Prior setting at 25–35 °C increased the breaking force of proteins compared to directly heated gel, resulting in maximum breaking force at 35 °C/60 min. However, the setting at 40 °C/30 min caused proteolysis, which was reflected in higher amounts of TCA‐soluble peptides and gel weakening. Denser microstructure and higher myosin heavy chain polymerisation observed in the gels which experienced the setting was well correlated with improvement in textural properties. Abstract : Schematic overview of blend protein isolate production from silver carp and kilka using the pH‐shift process followed by evaluating the effect of MTGase and setting condition of its gel properties.